P14.41 Cost-effectiveness of FET PET for early treatment response assessment in glioma patients following adjuvant temozolomide chemotherapy. (9th September 2021) - Rosen, J; Ceccon, G; Bauer, E K; Werner, J M; Kabbasch, C; Fink, G R; Langen, K J; Galldiks, N
Abstract: BACKGROUND: In light of increasing healthcare costs, higher medical expenses should be justified socio-economically. Therefore, we calculated the effectiveness and cost-effectiveness of PET using the radiolabeled amino acid O-(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET) compared to conventional MRI for early identification of responders to adjuvant temozolomide chemotherapy. A recent study in IDH-wildtype glioma patients suggested that after two cycles, FET-PET parameter changes predicted a significantly longer survival while MRI changes were not significant. MATERIALS AND METHODS: To determine the effectiveness and cost-effectiveness of serial FET-PET imaging, we analyzed published clinical data and calculated the associated costs in the context of the German healthcare system.Based on a decision-tree model, FET-PET and MRI's effectiveness was calculated, i.e., the probability to correctly identify a responder as defined by an overall survival ≥15 months. To determine the cost-effectiveness, the incremental cost-effectiveness ratio (ICER) was calculated, i.e., the cost for each additionally identified responder by FET-PET who would have remained undetected by MRI. The robustness of the results was tested by deterministic and probabilistic (Monte Carlo simulation) sensitivity analyses. RESULTS: Compared to MRI, FET-PET increases the rate of correctly identified responders to chemotherapy by 26%; thus, four patients need to be examined by FET-PET to identify one additional responder. Considering the respective cost for serial FET-PET and MRI, the ICER resulted in €4, 396.83 for each additional correctly identified responder by FET-PET. The sensitivity analyses confirmed the robustness of the results. CONCLUSION: In contrast to conventional MRI, the model suggests that FET PET is cost-effective in terms of ICER values. Concerning the high cost of temozolomide, the integration of FET-PET has the potential to avoid premature chemotherapy discontinuation at a reasonable cost.